Competitive intelligence and decision problems - David, Amos (ISTE., 2011)
The development of a research, teaching, or application of competitive (economic) intelligence requires a strategic and transverse vision in regards to related issues. It is essential to integrate the role of culture when interpreting results, either from the training of a specialist or in respect to a country or region. The authors of this book, members of an expert group supported by the CNRS in France, bring all of their talents together to create a comprehensive book that does just this and more.